Pengaruh Self Efficacy, Financial Literacy, dan Financial Inclusion Terhadap Fintech Payment Use - Adzhani, Nazula; Sanistasya, Poppy Alvianolita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research investigates the use of fintech payments among Samarinda’s urban population, with the objective of evaluating how self-efficacy, financial literacy, and financial inclusion impact the use of fintech payments. The study employs a quantitative methodology, utilizing multiple linear regression analysis, and the data is processed using SPSS 30 software. Data for the research was collected through observations, documentation, literature reviews, and questionnaires distributed to 100 individuals who utilize fintech payments in Samarinda City. The study's findings revealed that self-efficacy did not significantly influence the use of fintech payments, with a significance level of 0,420 > 0,05 however, financial literacy significantly affected the use of fintech payments, with a significance level of 0,018 < 0,05. Furthermore, financial inclusion also had a significant impact on the use of fintech payments, with a significance level of 0,019 < 0,05. Additionally, when considering all three factors together self-efficacy, financial literacy, and financial inclusion they collectively demonstrated a significant effect on the use of fintech payments, represented by a significance level of 0,001 < 0,05. The outcomes of this research offer insight into the adoption of fintech payments within the Samarinda City community, highlighting the importance of enhancing self-efficacy alongside the existing levels of financial literacy and financial inclusion.